Acarocybellina arengae - A new generic and species record from India - NEELIMA A. MOONNAMBETH, RASHMI DUBEY* and (Indian Phytopathology, 2013)
During a routine survey for collection of foliicolous fungi to Sawantwadi forest areas in Sindhudurg District of Maharashtra a new fungus was encountered growing on spadix of Cocos nucifera L. (family Arecaceae). The fungus generally causes black mildew symptoms which cover 70% of the plant parts. On critical microscopic examination the fungus was identified as Acarocybellina arengae Subramanian (11) and was found new to the country. The genus was established by Subramanian in the year 1992 after conducting studies on morhotaxonomic behavior of Sporidesmium arengae. According to Subramaninan (11) Sporidesmium arengae described by Matsushima (7) on Arenga engleri from Ishigaki island, Japan is not a species of Sporidesmium because in the present genus the simple, brown, septate conidiophores proliferate in characteristic fashion somewhat as in Acarocybella jasminicola Hansf.